Antibiogram Pattern of Escherichia coli, Salmonella spp. and Staphylococcus spp. Isolates from Broiler Chicken - Khanal, S.; Kandel, M.; Shah, M. P. (Nepalese Veterinary Journal, 2019)
This study was conducted on clinical cases of broiler chicken brought at National Avian Disease Investigation Laboratory (NADIL) and Veterinary Teaching Hospital, Agriculture and Forestry University during the period of December, 2018 to April, 2019. The study was aimed to find the antibiogram pattern of Escherichia coli, Salmonella species and Staphylococcus species. A total of 50 ill broiler liver samples were collected and inoculated in Nutrient Agar, XLD agar Mac-Conkey agar, EMB Agar and Mannitol Salt Agar and incubated for 24 hours at 370C. During microbiological examination, prevalence of E.coli was 36 %, Salmonella species was 2% and Staphylococcus species was 8% where as mixed infection was 40%. Antibiogram profile for E. coli isolates were sensitive to Amikacin (88.89%) followed by Colistin (66.67%), Ciprofloxacin (50%), Levofloxacin (42.10%) and Gentamycin (27.78%) while Ceftriaxone (11.11%) and Tetracycline (11.11%) was recorded as least sensitive, for Salmonella species isolates were highly sensitive to Amikacin (100%) and other remaining antibiotics; Ceftriaxone , Gentamicin, Levofloxacin, Ciprofloxacin, Colistin and Tetracycline were observed to be resistant and for Staphylococcus spp. isolates were sensitive to Amikacin (75%) followed by Gentamicin (25%) , Levofloxacin (25%), and Ciprofloxacin (25%) while Tetracycline and Colistin were resistant. In the conclusion, it is strongly recommended to decrease the unethical use of antibiotics to minimize the development of resistance strain of microbes in the future.